"Obviously, we're all oil industry": The criminogenic structure of the offshore oil industry. (August 2015) - Bradshaw, Elizabeth A
The 2010 BP Gulf of Mexico oil spill was one of the worst environmental disasters in the United States. The deviant actions of state and corporate actors involved in the Gulf of Mexico spill are not unique, but instead are symptomatic of a problem rooted much deeper in the US oil and gas industry. Building on Michalowski and Kramer's Integrated Theoretical Model of State–Corporate Crime, this article explores the industry as a level of analysis. Early studies of white-collar crime that examined criminality within industries tended to approach the problem from the individual level and failed to consider the role of government in shaping the structural conditions of an industry. This article introduces the concept of "criminogenic industry structures" and examines the historical role of the federal government in shaping the criminogenic conditions of the offshore oil drilling industry that resulted in the 2010 Gulf of Mexico oil spill.